Oryza sativa BRASSINOSTEROID UPREGULATED1 LIKE1 Induces the Expression of a Gene Encoding a Small Leucine-Rich-Repeat Protein to Positively Regulate Lamina Inclination and Grain Size in Rice - Jang, Seonghoe; Li, Hsing-Yi (Frontiers in Plant Science, 2017)
Oryza sativa BRASSINOSTEROID UPREGULATED1 LIKE1 (OsBUL1) positively affects lamina inclination and grain size. OsBUL1 knock-out (osbul1) plants as well as transgenic rice with reduced level of OsBUL1 expression produce erect leaves and small grains. Here, we identified a putative downstream gene of OsBUL1, OsBUL1 DOWNSTREAM GENE1 (OsBDG1) encoding a small protein with short leucine-rich-repeats by cDNA microarray analyses in the lamina joint and panicles of wild-type and osbul1 plants. Transgenic rice plants with increased OsBDG1 expression exhibit increased leaf angle and grain size, which is similar to an OsBDG1 activation tagging line whereas double stranded RNA interference (dsRNAi) lines for OsBDG1 knock-down generate erect leaves with smaller grains. Moreover, transgenic rice expressing OsBDG1 under the control of OsBUL1 promoter also shows enlarged leaf bending and grain size phenotypes. Two genes, OsAP2 (OsAPETALA2) and OsWRKY24 were identified as being up-regulated transcriptional activators in the lamina joint of pOsBUL1:OsBDG1 plants and induced expression of the two genes driven by OsBUL1 promoter caused increased lamina inclination and grain size in rice. Thus, our work demonstrates that a series of genes showing expression cascades are involved in the promotion of cell elongation in lamina joints and functionally cause increased lamina inclination.